In-season integrative neuromuscular strength training improves performance of early-adolescent soccer athletes - Panagoulis, C.; Chatzinikolaou, A.; Avloniti, A.; Leontsini, D.; Deli, C. K.; Draganidis, D.; Stampoulis, T.; Oikonomou, T.; Papanikolaou, K.; Rafailakis, L.; Kambas, A.; Jamurtas, A. Z.; et al. (The Journal of Strength and Conditioning Research, 2020)
Although forms of integrative neuromuscular training (INT) are used extensively for injury prevention and treatment, no information exists about its effects on performance of adolescent athletes. We investigated the effects of an in-season INT intervention on performance of early-adolescent players using a 2-group, repeated-measures design. Twenty-eight early adolescents were randomly assigned to a control group (CG, participated only in soccer training, N = 14, 11.4 ± 0.57 years, Tanner stage 2.8 ± 0.6) or an experimental group (INT was added to conventional soccer training, N = 14, 11.2 ± 0.5 years, Tanner stage 2.6 ± 0.5). Integrative neuromuscular training (8 weeks, 3 sessions/wk) aimed to develop core strength, hamstrings eccentric strength, hip/knee musculature, and dynamic stability using body mass exercises, medicine balls, rocker boards, Bosu, stability balls, etc. Ball shooting speed, speed (10, 20-m), change of direction (COD), jumping performance, and strength were measured before and after training. A 2-way repeated-measures ANOVA was used to analyze data. Integrative neuromuscular training improved 10- and 20-m speed (2.52-2.13 and 3.61-3.39 seconds, respectively, p < 0.05), strength (40.1-44.4 kg, p < 0.05), jumping ability (squat jump: 16.3-17.9 cm; countermovement jump: 19.1-20.3 cm, p < 0.05), COD (18.0-17.3 seconds, p < 0.05), and shooting speed (73.8-79.0 km/h, p < 0.05). In the CG, soccer training caused an improvement of smaller magnitude in 10 m and shooting speed (p < 0.05), whereas COD and jumping performance remained unaffected while 20-m speed, COD, and strength deteriorated. These results indicate that an 8-week INT program may induce positive adaptations in performance of early-adolescent soccer players during in-season training, suggesting that INT may be an effective training intervention for this age group.